Induction of heat stress tolerance in economically important Tomato (Solanum lycopersicum): A review on current knowledge - Mahmood-ur-Rehman, Muhammad; Nijabat, Aneela; Kazmi, Abeer; Ali, Amir; Sultana, Tahira; Younas, Muhammad; Mashwani, Zia-ur-Rehman; Khan, Bilal Ahmad; Qayyum, Bushra; Ali, Aamir (Journal of Pure and Applied Agriculture, 2023)
Tomatoes (Solanum lycopersicum) are common foods that provide essential calories, vitamins, and minerals to almost 80% of the global population. Concerns about the impact of rising temperatures on tomato production have intensified as a result of recent global climate change. Heat stress disrupts the plant's critical physiological and biochemical processes. High temperatures suppress photosynthetic activity and chlorophyll concentration, as well as pollen germination, fruit set, and ripening. Heat stress accumulates reactive oxygen species (ROS), which cause significant oxidative destruction to the crop. Heat shock proteins are produced swiftly by plants to reduce the effects of heat stress. A variety of factors determine heat tolerance including chlorophyll fluorescence, canopy temperature, membrane stability, plant water status, secondary metabolite synthesis, antioxidants, and associated enzymes. Knowledge of heat stress impact and tolerance at the biochemical, physiological, morphological, and molecular level at various growth phases (from seed germination to harvest) is critical for developing new crop types that can cope with future climate. To better understand the process underpinning stress tolerance and the generation of heat-tolerant cultivars, further research on the advanced genetic approaches like genome wide association mapping (GWAS), microarray, CRISPR Cas gene knockout editing and virus induced gene silencing (VIGS) in tomato seedlings under heat stress is required. © 2021 Department of Agricultural Sciences, AIOU